Japan - Pitts, Forrest Ralph, 1924- (Grand Rapids, Mich. : Fideler Co., 1962)
A social studies textbook for the upper elementary grades describing the geography, history, people, culture, and economy of Japan.
Includes index.
Keywords: Japan -- Juvenile literature; Japan